Mechanism of astaxanthin relieving lipopolysaccharide (LPS)-induced acute liver injury in mice - Min He; Xin-Yi Deng; Yan-Bin Zhu; Jie Hao; Matthew Kay; Hua Zhang; Jin Jun Chen; Zhi-Bao Chen (Ciência Rural, 2023)
ABSTRACT: Acute liver injury (ALI) is an important medical problem that requires effective therapy. Astaxanthin (AST) is a carotenoid, and the beneficial effects of astaxanthin, including anti-oxidative, anti-inflammatory and anti-tumour activities, have been identified. The present study was designed to elucidate the protective effects of astaxanthin against ALI and their underlying mechanisms. RAW264.7 macrophages were treated with dimethyl sulfoxide combined with different doses of astaxanthin for 12 h. Mice were fed with or without astaxanthin for up to 7 days. LPS was administered to induce inflammation. We assessed histopathology, oxidative stress, inflammation and apoptosis .The results indicated that astaxanthin attenuated LPS-induced oxidative stress, inflammation and cell apoptosis both in vivo and in vitro. In vivo and in vitro experiments showed that astaxanthin down regulated the nuclear factor-kappa beta (NF-κB), nuclear factor erythroid 2-related factor 2 (Nrf2) and NLR family pyrin domain containing 3 (NLRP3) signalling pathways, inhibiting the LPS-induced inflammatory response, oxidative stress and cell apoptosis, and alleviating LPS-induced ALI in mice.